Asymmetric spiders: Supplier heterogeneity and the organization of firms - Verena Nowak; Christian Schwarz; Jens Suedekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We consider a property rights model of a firm with two heterogeneous suppliers. The headquarters determine the firm's organizational structure, and we analyze which sourcing mode (outsourcing or vertical integration) is chosen for which of the asymmetric inputs. If suppliers' investment choices are strategic complements, the firm may keep the technologically more important input inside its boundaries and outsource the less important supplier. The firm also tends to keep more sophisticated inputs in-house, while choosing an external supplier organization for simpler and for low-cost components. These theoretical predictions are consistent with numerous case studies and recent empirical evidence on the internal organization of firms.
Keywords: D23; L23; F23; 330; firm organization; outsourcing; intra-firm trade; property rights approach